The Urgency of Border Area Development Towards Special Economic Zones: Legal Guarantees for Social Welfare in Indonesia - Zein, Yahya Ahmad; Rohman, Arif (Fakultas Hukum Universitas Lampung, 2024)
Border areas will continue to lag behind other regions without proper management. The limited natural resources in these areas pose a challenge for development. Through national strategic projects, border regions are expected to compete and enhance the well-being of their communities. This research aims to analyze the efforts of border regions in realizing Special Economic Zones (SEZs) to address regional disparities in Indonesia. Using doctrinal legal research with a legislative approach and comparative studies, the findings show that establishing SEZs in border areas, specifically North Kalimantan, provides a legal guarantee that facilitates economic functions. This will accelerate economic development in North Kalimantan and nationally, promote infrastructure, and support sustainable, environmentally sound development, contributing to community welfare. Therefore, meeting SEZ regulations is part of a legal guarantee under responsive law..